Smart Glasses with Augmented Reality Workflow; A Modern Tool for Triage in Mass Casualty Incidents - Apiratwarakul, Korakot; Woon Cheung, Lap; Pearkao, Chatkhane; Ienghong, Kamonwon (Archives of Academic Emergency Medicine, 2025)
Introduction: Smart glasses with an augmented reality workflow have emerged as a new tool for triage in mass casualty incidents (MCIs). This study aimed to investigate the accuracy and time efficiency of smart glasses in MCIs triage. Methods: A retrospective field exercise study was conducted in November 2024 at EMS Srinagarind Hospital, Thailand. All participants performed self-assessments and used smart glasses for triage sieve. Data were recorded in terms of accuracy and time required for triage. Results: A total of 108 participants were enrolled, with a mean age of 33.4 years, of whom 57.4% were female. The smart glasses group achieved the highest accuracy in triage level 1, with 98.3% compared to 79.3% in the self-assessment group (P < 0.001). The smart glasses group also completed triage significantly faster than the self-assessment group, with a time of 23.5 versus 72.4 seconds for triage level 1 and 31.3 versus 89.1 seconds for level 2. Conclusion: The use of smart glasses with an augmented reality workflow for triage sieve in MCIs is beneficial, improving both accuracy and evaluation time for patients in triage levels 1 and 2.